Assessment and Mapping of Soil Quality Degradation Indicators for Some Desert Lands Using Geospatial Techniques - Oleiwi, Ali Khalid; Khalaf, Ayad Abdullah (Journal of Cultural Analysis and Social Change, 2026)
The aim of this study was to assess soil quality degradation in selected desert lands and to produce their geospatial maps using Geographic Information Systems (GIS). The study was conducted in Thi-Qar Governorate in southern Iraq, covering an area of 99.12 km². A total of 33 surface soil samples (0–30 cm) were collected, in addition to describing five soil pedons distributed across the study area following the guidelines of the Soil Survey Staff (2022). Physical indicators (texture, bulk density, porosity, and electrical conductivity), chemical indicators (gypsum, calcium carbonate, electrical conductivity, soil reaction, sodium adsorption ratio, and exchangeable sodium percentage), and fertility indicators (organic matter, available nitrogen, available phosphorus, and available potassium) were measured. Spatial distribution maps of soil quality indicators were generated using the Inverse Distance Weighting (IDW) spatial interpolation technique in ArcGIS. The results showed that the Soil Physical Index fell within the low class, representing 98.04 km² (98.91%). The Soil Chemical Index was distributed between the medium class with an area of 36.83 km² (37.16%) and the high class covering 62.29 km² (62.84%). The Soil Fertility Index was classified into three classes, with the medium class forming the largest area (91.27 km²). The Soil Quality Index (SQI) itself was distributed between two classes: the moderate class, which comprised 67.36 km² (67.96%), and the low class, which covered 31.76 km² (32.04%). This indicates that most of the soils fall within the moderate-to-poor quality categories that are amenable to improvement through sustainable management. The study concludes that integrating field and laboratory analyses with digital geospatial processing constitutes an effective tool for monitoring environmental changes and degradation in the soils of Thi-Qar.